Collaboration of the Department of Women's Empowerment and Child Protection, Population Control and Family Planning (DP3APPKB) and the Surabaya Children's Forum in Realizing a Child-Friendly City (KLA) in Surabaya - Vivi Rahmawati; Navira Gensa Mayla F; Windy Aprilia D; Erlino Dwi H; Bagus Nuari Hermawan (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract Children are valuable assets for the future of a nation, making the fulfillment of their rights and protection a priority in regional development. The Child-Friendly City (Kota Layak Anak) initiative in Surabaya aims to create a safe, supportive, and child-friendly environment that fosters optimal child development. This study examines the collaborative process among various stakeholders, particularly the Department of Women’s Empowerment, Child Protection, Population Control, and Family Planning (DP3APPKB) and the Child Forum, in realizing the Child-Friendly City in Surabaya. Using a qualitative case study approach through interviews, observations, and documentation, the findings indicate that effective collaboration is characterized by open communication, clear role distribution, and mutual commitment among stakeholders. This collaboration enhances children’s participation in decision-making and the implementation of KLA programs. The study highlights the importance of cross-sector synergy and child empowerment as key elements in developing a Child-Friendly City. The findings can serve as a reference for other local governments in developing effective collaborative models for comprehensive child rights fulfillment. Keywords: Child-friendly city, Child forum, Child rights fulfilment, Collaboration.